HRM practices of knowledge intensive and non-knowledge intensive SMEs and its relationship with employees competencies - Hashim, Junaidah (s.n, 2012)
The purpose of this study is twofold: firstly, to examine the formality of HRM practices among knowledge-intensive and non-knowledge-intensive SMEs in Malaysia and secondly, to compare the practices between the two types of SMEs. A survey was administered to ascertain whether there are differences, if any, in the employees competencies in both types of SMEs. The same instrument also evaluates whether there are relationships, if any, between HRM practices and employees competencies